Coaches' evaluations of match performance in academy soccer players in relation to the adolescent growth spurt - Hill, M.; Scott, S.; McGee, D.; Cumming, S. (Journal of Science in Sport and Exercise, 2020)
Individual differences in biological maturation present challenges for coaches involved with youth soccer players. Youth in the same chronological age group vary in terms of stage of maturity (pre, circum- and post-pubescent) and rate of growth, but how this affects coaches` evaluations of player performance is unknown. The aim of this study was to compare youth soccer coaches` evaluations of players match performances before, during and post growth spurt in a professional English soccer academy across four seasons. Two hundred and seventy-eight male soccer players in the under-9 to under-16 age-groups had their performances evaluated by their coach on a 4-point Likert scale. For each game, players were categorised by their maturity status estimated using percentage of predicted adult height at the time of observation. A one-way ANCOVA controlling for the level of opposition and game outcome revealed that coaches` evaluations declined from the pre- to during growth spurt stages, however, this was only significant in the under 12 age-group. Further, coaches` evaluations increased again in the post-growth spurt stage, although only significant in the under 15 age-group. Coaches evaluations of player performance appear to vary in accordance with stage of maturity and rate of growth. Practitioners in youth soccer should understand the extent to which maturity status may adversely impact performance and consider this when making talent selection decisions.